Influência da adesão vitreomacular na resposta terapêutica do Edema macular diabético com antiangiogênicos - Victor Ferreira Masson (2016)
Purpose: To investigate the effect of vitreomacular adhesion (VMA) on the outcome of intravitreous antiangiogenic treatment in patients with diabetic macular edema (DME) assessed by best-corrected visual acuity (BCVA) and by central retinal thickness (CRT). Method: Retrospective study of prospectively collected data in which patients from Instituto da Visão in Belo Horizonte (MG), Brazil were selected, between July 2012 and January 2014. The sample was classified by optical coherence tomography (OCT) images (Spectralis; Heidelberg Engineering,Heidelberg, Germany) in two groups: VMA+ and VMA-, according to the presence or absence of VMA, respectively. The patients were evaluated for BCVA and CRT before the first intravitreal injection and followed after the first, the 3rd and the 6th month. The treatment protocol was of one monthly injection in the first three months and reinjection as needed. The antiangiogenic drugs used were: Bevacizumab (Avastin®), Ranibizumab (Lucentis®) and Aflibercept (Eylea®). Results: 142 diabetic patients were selected and, from those, 195 eyes were included to take part in the study. A total of 83 eyes were classified as VMA- and 112 eyes as VMA+. The mean BCVA at baseline was similar in both groups (p=0.221). The mean CRT at baseline was different (p=0.022), and it was higher inthe VMA+ group. Between the baseline and the first month, in spite both groups had obtained BCVA improvement, the comparison between them showed a more significant improvement in the VMA- (p=0,016). At six months, there was no statistically significant difference for BCVA between the groups (p=0.622). Considering CRT, both groups obtained improvement between baseline and the first month. However, when the reduction in CRT was compared over a 6-month period, there was a greater reduction in CRT in the VMA- group (p<0.001). When the percentage reduction in CRT was compared between groups over a 6-month period, it was observed a greater reduction in CRT in the VMA- group as well (p=0.017). To verify if others factors, besides VMA, were associated with changes in visual acuity and CRT at 1 month, a multiple linear regression analysis was performed. This analysis revealed that for 1-month visual acuity, 77% of its variability was related mainly to the baseline BCVA. VMA contributed with 3% in this model. As to the CRT, this analysis revealed that 57% of its variability was related mainly to the CRT baseline. VMA contributed with 10% in this evaluation. Conclusion: Despite the similar behavior between groups over a 6-month period,the VMA- group had a more significant improvement in BCVA and a moresignificant reduction in CRT. In the multiple linear regression analysis VMA was one of the variables of influence in the responses of BCVA and CRT to treatment at 1 month, suggesting that its presence can be an